Динамические параметры асинхронных двигателей частотно-регулируемых электроприводов - Акимов, Л.В.; Котляров, В.О.; Литвиненко, Д.Г. (Електротехніка і електромеханіка, 2011)
In the article, various designations of physical quantities used in scientific and technical literature for description of vector and scalar control systems are unified. Actual values of dynamic parameters of machines are defined on examples of domestic and foreign serial asynchronous motors.